2011
DOI: 10.1371/journal.pone.0019465
|View full text |Cite
|
Sign up to set email alerts
|

Situational and Dispositional Determinants of Intentional Deceiving

Abstract: Does opportunity make the thief or are people dispositionally prone to deceive? The interaction between personality and the circumstances surrounding deception is crucial to understand what promotes dishonesty in our society. Due to its inherent spontaneity and sociality, deceptive behaviour may be hardly reproducible in experimental settings. We developed a novel paradigm in the form of an interactive game where participants can choose whether to lie to another person in situations of loss vs. gain, and of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
77
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(107 citation statements)
references
References 29 publications
20
77
2
Order By: Relevance
“…However, some studies do not show this pattern. For example, Panasiti, Pavone, Merla, Aglioti, and Perc () did not find a direct relation between moral disengagement and lying. In the context of our experiment, it might be the case that by providing justification via counterfactual information, people did not need to rely on their ability to disengage the moral aspects from the situation in order to cheat, resulting in a null effect of moral disengagement on cheating.…”
Section: Discussionmentioning
confidence: 96%
“…However, some studies do not show this pattern. For example, Panasiti, Pavone, Merla, Aglioti, and Perc () did not find a direct relation between moral disengagement and lying. In the context of our experiment, it might be the case that by providing justification via counterfactual information, people did not need to rely on their ability to disengage the moral aspects from the situation in order to cheat, resulting in a null effect of moral disengagement on cheating.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we used an ecological paradigm for assessing deception (Panasiti et al ., , , ) in order to explore how social judgements along these two dimensions modulate the decision to lie to others. In this two‐person online card game, participants are always entirely free to decide whether to lie or tell the truth.…”
Section: Introductionmentioning
confidence: 99%
“…People high on social adroitness and extroversion reported telling more lies during social interactions, whereas people with higher quality of same-sex relationships reported less lies [5]. In one study the authors demonstrated that people high on manipulativeness and moral disengagement are less likely to refrain from lying when their reputation is at risk [8]. These results confirm that personality traits influence the likelihood of lying in different contexts.…”
Section: Introductionmentioning
confidence: 83%
“…Previous research has clearly indicated that the tendency to engage in deceptive behaviors is related to specific personality traits and contextual factors [3][4][5][6]8,10]. Intellectual abilities are important for the quality of lies [26,31] and are related to deceptive communication style [32,33,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation